Association of Vaginal Microbiota With Signs and Symptoms of the Genitourinary Syndrome of Menopause Across Reproductive Stages. (27th April 2021) - Shardell, Michelle; Gravitt, Patti E; Burke, Anne E; Ravel, Jacques; Brotman, Rebecca M
Abstract: The genitourinary syndrome of menopause (GSM) describes signs and symptoms resulting from effects of estrogen deficiency on the female genitourinary tract, including the vagina, labia, urethra, and bladder. Signs/symptoms associated with GSM may occur during any reproductive stage from multiple etiologies but are most common during menopause due to low estrogen. Vaginal microbiota, particularly Lactobacillus spp., are beneficial to the female genital tract; however, their abundance declines during menopause. We aimed to longitudinally assess vaginal microbiota characterized by 16S rRNA gene amplicon sequencing and GSM-associated endpoints across reproductive stages. In a 2-year cohort study of 750 women aged 35–60 years at enrollment and 2 111 semiannual person-visits, low- Lactobacillus vaginal microbiota communities were observed at 21.2% (169/798), 22.9% (137/597), and 49.7% (356/716) of person-visits among pre-, peri-, and postmenopausal women, respectively ( p < .001). Compared to communities that have high Gardnerella vaginalis relative abundance and diverse anaerobes, the following communities were associated with a lower covariate-adjusted odds of vaginal atrophy: L crispatus -dominated communities among postmenopausal women (odds ratio [OR] = 0.25; 95% confidence interval [CI]: 0.08, 0.81), L gasseri/L jensenii (OR = 0.21; 95% CI: 0.05, 0.94) and L iners (OR = 0.21; 95% CI: 0.05, 0.85) among perimenopausal women, and L iners -dominated communities (OR = 0.18; 95% CI: 0.04, 0.76) among premenopausal women. Postmenopausal women with L gasseri/L jensenii -dominated communities had the lowest odds of vaginal dryness (OR = 0.36; 95% CI: 0.12, 1.06) and low libido (OR = 0.28; 95% CI: 0.10, 0.74). Findings for urinary incontinence were inconsistent. Associations of vaginal microbiota with GSM signs/symptoms are most evident after menopause, suggesting an avenue for treatment and prevention.